2018
DOI: 10.3168/jds.2017-14253
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of bovine leukemia virus proviral DNA using a low-cost real-time polymerase chain reaction

Abstract: The detection of bovine leukemia virus (BLV) proviral DNA is an important tool to address whether an animal is infected with BLV. Compared with serological assays, real-time PCR accounts for greater sensitivity and can serve as a confirmatory test for the clarification of inconclusive or discordant serological test results. However, the high cost related to real-time PCR assays has limited their systematic inclusion in BLV surveillance and eradication programs. The aim of the present study was to validate a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 17 publications
0
23
0
2
Order By: Relevance
“…The low proviral loads in milk might be explained by the presence of numerous components in milk (i.e., proteases, complex polysaccharides, lipids, and Ca 2+ ions) that can interfere with DNA extraction and qPCR analysis, thereby, decreasing the detection sensitivity compared to that in the blood. Indeed, interference with PCR amplification was previously demonstrated when the limit of detection of BLV qPCR was assessed in the presence of the BLV provirus in a milk matrix [16]. Another explanation for the differences in proviral loads could be that less BLV-infected cells containing integrated BLV provirus are present in milk than in blood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The low proviral loads in milk might be explained by the presence of numerous components in milk (i.e., proteases, complex polysaccharides, lipids, and Ca 2+ ions) that can interfere with DNA extraction and qPCR analysis, thereby, decreasing the detection sensitivity compared to that in the blood. Indeed, interference with PCR amplification was previously demonstrated when the limit of detection of BLV qPCR was assessed in the presence of the BLV provirus in a milk matrix [16]. Another explanation for the differences in proviral loads could be that less BLV-infected cells containing integrated BLV provirus are present in milk than in blood.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was previously reported that BLV-infected cells were present in the milk and colostrum of BLV-positive dams, because inoculation of lambs with milk or viable milk cells from 24 dairy cattle naturally infected with BLV resulted in the detection of infectious virus in the milk of 17 cows [13]. Recently, BLV provirus was detected in field samples of milk and colostrum [1416]. However, the resistance of calves to milk-borne infection can be attributed to virus-neutralizing antibodies, which all calves nursed on BLV-positive dams acquire through the colostrum and retain in their serum for as long as 6 months [17, 18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PVL was quantified by a real-time quantitative PCR (qPCR), as previously reported [10,11,12]. Briefly, the SybrGreen chemistry was used, amplifying a region of 120 bp of the pol gene and 500 ng of DNA template.…”
Section: Methodsmentioning
confidence: 99%
“…The quantification of BLV proviral genome is an important diagnostic tool for BLV infection. Compared with serological assays, real-time PCR has high sensitivity and can act as a confirmatory test for the clarification of inconclusive or discordant serological test results (Petersen et al, 2018). However, BLV provirus cannot be detected by real-time PCR in some BLV-infected cattle (not published).…”
Section: Discussionmentioning
confidence: 99%